PENGARUH BAHAN AJAR MODEL PROBLEM BASED LEARNING TERHADAP AKTIVITAS DAN PEMAHAMAN SISWA TERHADAP MATERI AJAR DI KELAS V SEKOLAH DASAR - Lina Marcelina; Desyandri (STKIP Subang, 2023)
This research is motivated by the activity and understanding of fifth grade students at SDN 57 Anak Air Kumayan, Lubuk Basung District, which is still low. It can be seen that many students are less enthusiastic in learning. This research was conducted on class students at SDN 57 Anak Air Kumayan, Lubuk Basung District, for the 2022/2023 academic year. The experimental research design used is the randomized control group only design. Students' understanding for the significance level α = 0.05 and dk = 38 obtained a Tcount of -1.385, while Ttable = 2.0244. It can be concluded that Ho is accepted because tcount < ttable. Thus it can be concluded that there is no significant difference in students' initial understanding before being treated in the experimental class and the control class. Furthermore, based on the results of the t test on the posttest results shown in the table, the tcount is 3.418, while ttable = 2.0244. It can be concluded that H1 is accepted because tcount > ttable. Thus it can be concluded that there are differences in students' understanding after being taught with teaching materials with the Problem Based Learning (PBL) model in the experimental class and student learning outcomes taught with conventional learning in the control class